Global Profiling of Lysine Acetylation in Borrelia burgdorferi B31 Reveals Its Role in Central Metabolism - Bontemps-Gallo, Sébastien; Gaviard, Charlotte; Richards, Crystal L.; Kentache, Takfarinas; Raffel, Sandra J.; Lawrence, Kevin A.; Schindler, Joseph C.; Lovelace, Joseph; Dulebohn, Daniel P.; Cluss, Robert G.; Hardouin, Julie; Gherardini, Frank C. (Frontiers in Microbiology, 2018)
The post-translational modification of proteins has been shown to be extremely important in prokaryotes. Using a highly sensitive mass spectrometry-based proteomics approach, we have characterized the acetylome of B. burgdorferi. As previously reported for other bacteria, a relatively low number (5%) of the potential genome-encoded proteins of B. burgdorferi were acetylated. Of these, the vast majority were involved in central metabolism and cellular information processing (transcription, translation, etc.). Interestingly, these critical cell functions were targeted during both ML (mid-log) and S (stationary) phases of growth. However, acetylation of target proteins in ML phase was limited to single lysine residues while these same proteins were acetylated at multiple sites during S phase. To determine the acetyl donor in B. burgdorferi, we used mutants that targeted the sole acetate metabolic/anabolic pathway in B. burgdorferi (lipid I synthesis). B. burgdorferi strains B31-A3, B31-A3 ΔackA (acetyl-P- and acetyl-CoA-) and B31-A3 Δpta (acetyl-P+ and acetyl-CoA-) were grown to S phase and the acetylation profiles were analyzed. While only two proteins were acetylated in the ΔackA mutant, 140 proteins were acetylated in the Δpta mutant suggesting that acetyl-P was the primary acetyl donor in B. burgdorferi. Using specific enzymatic assays, we were able to demonstrate that hyperacetylation of proteins in S phase appeared to play a role in decreasing the enzymatic activity of at least two glycolytic proteins. Currently, we hypothesize that acetylation is used to modulate enzyme activities during different stages of growth. This strategy would allow the bacteria to post-translationally stimulate the activity of key glycolytic enzymes by deacetylation rather than expending excessive energy synthesizing new proteins. This would be an appealing, low-energy strategy for a bacterium with limited metabolic capabilities. Future work focuses on identifying potential protein deacetylase(s) to complete our understanding of this important biological process.